BIOLOGICAL AND ENVIRONMENTAL PECULIARITIES OF INTRODUCTION OF WASHINGTONIA FILIFERA (LIND. EX ANDR.) H. WENDL. EX BARY AT THE SOUTHERN COAST OF CRIMEA - Yuriy V. Plugatar; Alexandr P. Maksimov; Maksim S. Kovalev; Valeriy D. Rabotyagov; Natalya N. Trikoz; Alexandr F. Khromov (Юг России: экология, развитие, 2018)
Abstract. Aim of this research is to study winter resistance, drought resistance, resistance to fungal diseases and harmful insects of Washingtonia filifera (Lind. ex Andr., H. Wendl. ex A. Bary, 1879) and to examine the possibility of the subsequent selection using the experimental mutagenesis for increasing its frost resistance at the Southern Coast of the Crimea (SCC). Material and methods. The material and objects of our research were the collection plantations of Washingtonia filifera in the Arboretum of Nikitsky Botanical Garden (NBG) and parks of the South Coast of Crimea. Research methods: comparative-ecological, biometric, analytical and visual. To achieve the objective, the following results were obtained in the course of the studies. The history of introduction of this species in the NBG has been described and its occurrence at the Southern Coast of the Crimea (SCC) shown. An analysis of the quantitative biometric indicators of the leaves’ growth and die-back on average over the vegetation period on the basis of phenological observations over the test plants has been carried out taking into consideration the existing agricultural background. The reasons and factors influencing the frost resistance of this species depending on the combination of the set of meteorological indicators causing a certain level of frosting depending not only on the minimum negative temperatures but also on the soil and atmospheric moisture have been identified. Thresholds values of the impact of extreme negative temperatures for the Washingtonia filifera at the lethal and sub-lethal levels have been identified. Danger of infection of the representatives of the Arecaceae family (Arecaceae C.H. Schultz) with the new types of dangerous phytophages has been identified. The possibility of its selection with the use of a mutagen – colchicine has been shown. Main conclusions. The criteria have been outlined which will give the opportunity in the future to provide the science-based recommendations as to the agrotechnics of cultivation of this species under conditions of the SCC.